Teratoid Wilms Tumor and Classical Wilms Tumor: A Retrospective 10-Year Single-Center Study and Literature Review - Wu, Wei; Wu, Yibo; Xu, Weijue; Liu, Jiangbin; Lv, Zhibao (Frontiers in Surgery, 2022)
Background Wilms tumor (WT) is the most common renal tumor in the pediatric population. Nevertheless, teratoid Wilms tumor (TWT) is a rare category of WT characterized by different tissue types, and fewer than 70 cases have been reported in the literature to date. Methods A total of 67 WT patients admitted in our hospital from 2010 to 2020, including 5 patients with TWT, were enrolled in this study. The clinical features, preoperative and postoperative chemotherapeutic regimens, intraoperative findings, histopathological information, as well as prognoses of the WT patients were evaluated. Results TWT cases were matched to classical WT cases at 1:3 for the comparison of various variables. 7.46% (5/67) of WT patients were diagnosed with TWT. the tumor volume was dramatically larger for patients with TWT than for those with classical WT (203.30 ± 109.89 cm3 vs. 104.30 ± 66.97 cm3). However, the tumor weight of the two groups was similar (471.00 ± 80.65 vs. 432.67 ± 109.25). Conclusions Our data with the first reported Chinese children with TWT, preliminarily demonstrated that chemotherapy combined with surgery might be the appropriate treatment option for patients with WT, and prognoses of these patients differed sharply due to various stages. The density of TWT might be lower than that of classical WT. Future studies with more basic research to understand the biologic nature and theranostic markers of teratoid WT, may help us optimize the patient-tailored therapy of this rare type of WT.